The Response Patterns of the Career Interest Instrument Based on Holland’s Theory - Farida Agus Setiawati; Yulia Ayriza; Endah Retnowati; Rizki Nor Amelia (ANIMA Indonesian Psychological Journal, 2017)
This study aims to identify: patterns of responses, the item parameters, and the possibility of gender bias in the career interest instrument developed by the authors based on the Holland’s theory. The sample of this study was 576 elementary students in Daerah Istimewa Yogyakarta who were recruited using the cluster random sampling method. Two parameters were employed to analyze the response patterns using BILOG program. The results were: (1) three items have inappropriate response patterns to the model; (2) all items of the career interest instrument showed good item parameter criteria; and (3) ten items were identified containing Differential Item Functioning (DIF) in relation to gender bias as shown by the Item Characteristic Curve (ICC). The implications of this study are this instrument can be used in assesing career interest of students and the information of biased items may be considered in the selection of careers for male and female students, including in scoring and interpretation.